2011
DOI: 10.1108/03684921111169440
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian highways from slime mold's point of view

Abstract: Purpose -This paper seeks to develop experimental laboratory biological techniques for approximation of existing road networks, optimizing transport links, and designing alternative optimal solutions to current transport problems. It studies how slime mould of Physarum polycephalum approximate highway networks of Brazil. Design/methodology/approach -The 21 most populous urban areas in Brazil are considered and represented with source of nutrients placed in the positions of slime mould growing substrate corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 32 publications
(47 reference statements)
1
8
0
Order By: Relevance
“…There are several slime mold related applications can be found in the literature (Umedachi et al 2010;Tero et al 2010;Adamatzky and Oliveira 2011;Li et al 2011;Shann 2008) To implement SSOA, the following steps need to be performed (Li et al 2011):…”
Section: Fundamentals Of Slime Mold Algorithmmentioning
confidence: 99%
“…There are several slime mold related applications can be found in the literature (Umedachi et al 2010;Tero et al 2010;Adamatzky and Oliveira 2011;Li et al 2011;Shann 2008) To implement SSOA, the following steps need to be performed (Li et al 2011):…”
Section: Fundamentals Of Slime Mold Algorithmmentioning
confidence: 99%
“…That is why they are becoming more and more popular nowadays. Among them, there is a large organism called Physarum polycephalum, which is shown to be capable of solving many graphic theoretical problems, such as network design (Adamatzky 2012a;Adamatzky, de Pedro, and Oliveira 2011;Adamatzky, Lees, and Sloot 2013;Tero et al 2010), the shortest path tree problem , the shortest path finding problem (Adamatzky 2012b;Nakagaki et al 2007), and road planning (Adamatzky and Jones 2010). Nakagaki, Yamada, and Tóth (2000) have shown that Physarum has the ability to find the minimum-length solution between two points in a labyrinth.…”
Section: Introductionmentioning
confidence: 99%
“…An early evaluation of the road‐modelling potential of P. polycephalum in 2007 (Adamatzky, 2007a) came to no definite conclusion. However, significant progress has been made since that time; such as has been reported in our recent papers on approximation of highways systems in the UK (Adamatzky and Jones, 2010), Mexico (Adamatzky et al , 2011), The Netherlands (Adamatzky et al , 2012), Iberia (Adamatzky and Alonso‐Sanz, 2011) and Brazil (Adamatzky and de Oliveir, 2011). For all of these countries we found that the network of protoplasmic tubes developed by P. polycephalum matches, at least partly, network of human‐made transport systems; though the closeness of fit varies from country to country.…”
Section: Introductionmentioning
confidence: 99%